Application of Hyphenated Techniques in Speciation Analysis of Arsenic, Antimony, and Thallium - Rajmund Michalski; Sebastian Szopa; Magdalena Jabłońska; Aleksandra Łyko (The Scientific World Journal)
Due to the fact that metals and metalloids have a strong impact on the environment, the methods of their determination and speciation have received special attention in recent years. Arsenic, antimony, and thallium are important examples of such toxic elements. Their speciation is especially important in the environmental and biomedical fields because of their toxicity, bioavailability, and reactivity. Recently, speciation analytics has been playing a unique role in the studies of biogeochemical cycles of chemical compounds, determination of toxicity and ecotoxicity of selected elements, quality control of food products, control of medicines and pharmaceutical products, technological process control, research on the impact of technological installation on the environment, examination of occupational exposure, and clinical analysis. Conventional methods are usually labor intensive, time consuming, and susceptible to interferences. The hyphenated techniques, in which separation method is coupled with multidimensional detectors, have become useful alternatives. The main advantages of those techniques consist in extremely low detection and quantification limits, insignificant interference, influence as well as high precision and repeatability of the determinations. In view of their importance, the present work overviews and discusses different hyphenated techniques used for arsenic, antimony, and thallium species analysis, in different clinical, environmental and food matrices.